NILAI SPIRITUAL DALAM NOVEL WA’ALAIKUMUSSALAM, PELENGKAP IMAN KARYA IMA MADANIAH - Nur'alim, Muhammad; Usman, Usman; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms of spiritual values in the novel Wa’alaikumussalam, Pelengkap Iman by Ima Madaniah. This study employs a descriptive qualitative approach. The data sources for this study are sentences, phrases, or dialogues from the novel Wa’alaikumussalam, Pelengkap Iman by Ima Madaniah. The data collection techniques used in this study are reading and note-taking. The results of the study indicate that the forms of spiritual values in the novel Wa’alaikumussalam, Pelengkap Iman by Ima Madaniah are revealed in depth through its intrinsic elements, such as characters, setting, and point of view. The forms of spiritual values identified are compassion, empathy, patience, honesty, integrity, gratitude, trust, responsibility, and purity of heart